New venture analysis : research, planning, and finance - Costello, Dennis (Homewood, Ill. : Dow Jones-Irwin, 1985)
This book is about ideas on how to do a better job dealing with new ventures within your company. It intended to give practicing business managers, analysts, and business students about how to select the most promising research and development projects; ideas about how to better understand the markets, competitors, costs, and uncertainties facing your new ventures; ideas about how to finance your new ventures; and even ideas on how to generate new ventures ideas.
Includes index.
Includes bibliographical references: p.179-184.
hza 13/07/2018
Loans
Keywords: New products; Research, Industrial; Venture capital